Program Pendampingan Keluarga Bermasalah Kesehatan sebagai Upaya Percepatan Penurunan Stunting - Fahmi Hafid; Nasrul Nasrul; Nurjaya Nurjaya; Amsal Amsal; Nurfatimah Nurfatimah; Tjitrowati Djaafar; Herlina Susanto Sunuh; Artika Dewie; Andi Fatmawati Syamsu; Hadriani Hadriani; Dwi Yogyo Suswinarto; Lisnawati Lisnawati; Mardiani Mangun; Fitria Masulili; Baiq Emy Nurmalisa; Sri Restu Tempali; Helena Pangaribuan; Lindanur Sipatu; Fransisca Noya; Dafrosia Darmi Manggasa; Dewi Nurviana Suharto (Poltekita: Jurnal Pengabdian Masyarakat, 2022)
The prevalence of stunting in Sigi Regency showed an increase from year to year by 27.67% to 40.7%. The problem of stunting is a multidimensional problem that requires efforts from all parties to overcome it. One of the activities that can be done is to provide assistance to families with health problems or families at risk of stunting so that families can identify, assess, and take action independently accompanied by health workers. The implementation of this activity starts from 22-28 October 2022 in Beka Village, Marawola District. The socialization of the activity was attended by 50 people consisting of the village government, community leaders, PKK women, posyandu cadres, and target families. The targets of this activity are families with stunted children, pregnant women, teenagers/productive age, or breastfeeding mothers. His service activities include measuring body length/height, counseling on stunting, providing additional food, providing developmental stimulation, assisting cadres in filling out KMS, and KB MKJP education for mothers. The results of this activity program were very well appreciated by the local government, there was a change in knowledge about stunting, families who received assistance were very accepting of this activity and realized the importance of preventing stunting from the First 1000 Days of Life (HPK). It is hoped that this activity can take place continuously, families and communities can be independent in preventing stunting. ABSTRAK Prevalensi stunting di Kabupaten Sigi menunjukkan kenaikan dari tahun ke tahun sebesar 27,67% menjadi 40,7%. Masalah stunting merupakan masalah multidimensional sehingga butuh upaya dari semua pihak untuk mengatasinya. Salah satu kegiatan yang bisa dilakukan adalah melakukan pendampingan kepada keluarga dengan masalah kesehatan atau keluarga dengan risiko stunting sehingga keluarga bisa mengenali, menilai, dan melakukan tindakan secara mandiri yang didampingi oleh tenaga kesehatan. Pelaksanaan kegiatan ini dimulai dari tanggal 22-28 Oktober 2022 di Desa Beka Kecamatan Marawola. Sosialisasi kegiatan dihadiri 50 orang yang terdiri dari pemerintah desa, tokoh masyarakat, ibu PKK, kader posyandu, dan keluarga sasaran. Sasaran dari kegiatan ini adalah keluarga yang memiliki anak stunting, ibu hamil, remaja/usia produktif, atau ibu menyusui. Kegiatan pengabdiannya berupa pengukuran panjang badan/tinggi badan, penyuluhan tentang stunting, pemberian makanan tambahan, pemberian stimulasi perkembangan, pendampingan kader dalam pengisian KMS, dan edukasi KB MKJP kepada ibu. Hasil dari program kegiatan ini sangat diapresiasi dengan baik oleh pemerintah setempat, adanya perubahan pengetahuan tentang stunting, keluarga yang mendapatkan pendampingan pun sangat menerima dengan baik kegiatan ini dan menyadari pentingnya pencegahan stunting dari 1000 Hari Pertama Kehidupan (HPK). Diharapkan kegiatan ini dapat berlangsung secara kontinyu, keluarga dan masyarakat bisa mandiri dalam pencegahan stunting.